295 DO WOMEN FOLLOWING TRADITIONAL CHINESE POSTPARTUM PRACTICES OBTAIN LESS CERVICAL CANCER SCREENING IN NORTH AMERICA?. (1st January 2006) - Thai, H.; Jackson, C.; Huntington, J.
Abstract : Introduction: Asian Americans make up a sizable minority in the US, with Chinese currently making up the largest subgroup. However, despite this fact, the majority of Chinese women in North America underutilize Pap testing and carry a disproportionately higher rate of invasive cervical cancer. It has been suggested that certain cultural beliefs and practices can interfere with Western health care utilization among newly arrived immigrant communities. Methods: Fifteen hundred thirty-two women ages 20 to 69 from Seattle, Washington and Vancouver, BC were interviewed in person in 1999, and data from 993 participants were analyzed. Results: Women who observed postpartum rituals or who believed that certain aspects of their rituals help prevent them from obtaining cervical cancer did not show an underutilization of Pap testing. However, other factors, such as having a car in the household, speaking English, or being married, were highly predictive of Chinese women's Pap test utilizations. Discussion: Based on these findings, postpartum practices do not seem to negatively influence Pap test utilization among Chinese women in North America. Instead, clinicians serving Chinese in North America should focus more on economic, language, and acculturation as potential barriers for their patients' health care utilization.